2005
DOI: 10.1103/physreve.72.021101
|View full text |Cite
|
Sign up to set email alerts
|

System size stochastic resonance: General nonequilibrium potential framework

Abstract: We study the phenomenon of system size stochastic resonance within the nonequilibrium potential's framework. We analyze three different cases of spatially extended systems, exploiting the knowledge of their nonequilibrium potential, showing that through the analysis of that potential we can obtain a clear physical interpretation of this phenomenon in wide classes of extended systems. Depending on the characteristics of the system, the phenomenon results to be associated to a breaking of the symmetry of the non… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…It exhibits a broad resonance since for k not too large (indicating a high reflectiveness at the boundary or a reduced exchange with the environment) R increases with k, whereas it slightly decreases for larger k values (where the system's boundaries become absorbent). An explanation of this behavior in terms of the NEP has been given in [29]: as already observed, the NEP's symmetry is broken for this value of y L ; moreover, whereas the lower branch in Fig. 2b goes rapidly towards the value corresponding to Dirichlet's b.c.…”
Section: Results For Sssrmentioning
confidence: 97%
See 3 more Smart Citations
“…It exhibits a broad resonance since for k not too large (indicating a high reflectiveness at the boundary or a reduced exchange with the environment) R increases with k, whereas it slightly decreases for larger k values (where the system's boundaries become absorbent). An explanation of this behavior in terms of the NEP has been given in [29]: as already observed, the NEP's symmetry is broken for this value of y L ; moreover, whereas the lower branch in Fig. 2b goes rapidly towards the value corresponding to Dirichlet's b.c.…”
Section: Results For Sssrmentioning
confidence: 97%
“…The explanation offered in [27] to the phenomenon resorted to a collective variable X ≈ (1/N ) N j=1 x j , and to the fact that the noise in the effective stochastic differential equation for X scaled with size. In [29] it was shown that all the cases discussed in [27] can be put within the same NEP framework than the above studied scalar model. In fact, the aforementioned almost linear increasing dependence of ∆F 1 (y L ) on y L can be interpreted as a noise scaling with size.…”
Section: Results For Sssrmentioning
confidence: 99%
See 2 more Smart Citations
“…This symmetry-breaking phenomenon could be associated with the breaking of the symmetry of the nonequilibrium potential given by Eq. (2) [54]. In Fig.…”
Section: Resultsmentioning
confidence: 99%